STRUCTURAL OPTIMIZATION OF THE EXCAVATOR ENGINE HOOD BASED ON MODAL ANALYSIS - YANG WeiPing; HOU Liang; CAI HuiKun; LI ShengYu; ZHANG EnLai; WANG WenWu (Jixie qiangdu)
Excavator engine hoods are usually formed by welding sheet parts and stiffeners together. Under the incentives of engine and road,the sheet parts are easy to produce serious vibrational response,which directly results in the deformation and the cracking of some weak positions of the structure. The finite element model of an excavator engine hood was established and modal analysis was conducted by using Hyper Works software. Its first four order natural frequencies and corresponding mode shapes in free state were obtained. The accuracy of the simulation results were verified by a modal experiment. Based on the results of the modal experiment and the modal analysis,the structure of the engine hood was optimized. Comparing with the original structure,the stiffness of the optimized engine hood increased and the maximum deformation of typical modes decreased significantly,which indicates that its dynamic performance improves obviously.